2015
DOI: 10.1002/ddr.21242
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant‐Mediated Reversal of Oxidative Damage in Mouse Modeling of Complex I Inhibition

Abstract: Mitochondrial dysfunction is a key component of various aging-related pathologies of the brain that result in dementia. As such, it provides an important avenue in development of therapeutic interventions for a host of neurological disorders. A requirement for functional mitochondrial respiratory chain complex I (CI), to accomplish the normal physiological processes regulating memory, seems intuitive. In the present study, a synthetic lipoylcarnitine antioxidant (PMX-500FI; 100 mg/kg/day po) was administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…It is postulated that the antioxidant and antiinflammatory properties of AAM are the most important attributes of this compound [Hnia et al, 2007;Maczurek et al, 2008;Shenk et al, 2009;Mecocci and Polidori, 2012;Sozio et al, 2013;Salminen et al, 2014]. In addition, data from our labs Parameshwaran et al, 2015;Moos et al, 2016] and other studies [Karagiannis and Maulik, 2012;Karagiannis and Ververis, 2012] suggest epigenetic chromatin remodeling may also be involved [Aydin et al, 2012;Jakovcevski and Akbarian, 2012;Lunnon and Mill, 2013;Millan, 2013].…”
Section: Parkinson Diseasementioning
confidence: 73%
See 3 more Smart Citations
“…It is postulated that the antioxidant and antiinflammatory properties of AAM are the most important attributes of this compound [Hnia et al, 2007;Maczurek et al, 2008;Shenk et al, 2009;Mecocci and Polidori, 2012;Sozio et al, 2013;Salminen et al, 2014]. In addition, data from our labs Parameshwaran et al, 2015;Moos et al, 2016] and other studies [Karagiannis and Maulik, 2012;Karagiannis and Ververis, 2012] suggest epigenetic chromatin remodeling may also be involved [Aydin et al, 2012;Jakovcevski and Akbarian, 2012;Lunnon and Mill, 2013;Millan, 2013].…”
Section: Parkinson Diseasementioning
confidence: 73%
“…An optimal balance of BCL2 family proteins is essential in ensuring cell survival [Dixit et al, 2015;Denzer et al, 2016]. Parameshwaran et al [2015] showed that when mice were exposed to rotenone, the induced changes in increased BAX translocation to mitochondria and decreased phospho BCL-associated agonist of cell death were ameliorated by PMX-500FI.…”
Section: Synthetic Carnitine Esters (Carnitinoids)mentioning
confidence: 97%
See 2 more Smart Citations
“…In support of this concept, preliminary results from ongoing studies [Parameshwaran et al, ] show that PMX‐500FI can protect against neuromotor decline in vivo and restore deficits in long‐term potentiation (LTP) induced by rotenone exposure in mice. Thus, as demonstrated in Parameshwaran et al [], PMX‐500FI: Neutralizes synaptic LTP deficits, as evidenced by effects on field excitatory postsynaptic potentials (fEPSP) recorded following theta burst stimulation (Fig. ). Prevents declines in presynaptic release and basal synaptic transmission, also measured by effects on fEPSP amplitudes. Ameliorates declines in basal synaptic transmission, as shown by increased BAX protein translocation to mitochondria and decreases phosphorylated BCL‐associated agonist of cell death (BAD), as determined by western blot analysis. Inhibits decreases in phosphorylation of extracellular signal‐related kinase 1/2 (ERK1/2), as determined by western blot analysis. …”
Section: Novel Carnitinoids: Lipoic Acid Butyric Acid and Mitochondmentioning
confidence: 88%